2010
DOI: 10.1371/journal.pone.0013472
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of HrpL-Regulated Genes in the Necrotrophic Phytopathogen Dickeya dadantii 3937

Abstract: Background Dickeya dadantii is a necrotrophic pathogen causing disease in many plants. Previous studies have demonstrated that the type III secretion system (T3SS) of D. dadantii is required for full virulence. HrpL is an alternative sigma factor that binds to the hrp box promoter sequence of T3SS genes to up-regulate their expression.Methodology/Principal FindingsTo explore the inventory of HrpL-regulated genes of D. dadantii 3937 (3937), transcriptome profiles of wild-type 3937 and a hrpL mutant grown in a T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 49 publications
3
31
0
Order By: Relevance
“…HrpL readily formed insoluble inclusion bodies when overexpressed for protein purification, here (data not shown) and in previous studies (12, 27). Therefore, the solubility of HrpL and HrpL ΔR4.2 was maintained via copurification in complex with an E. coli RNAP with a His tag at the β subunit (28).…”
Section: Resultssupporting
confidence: 87%
“…HrpL readily formed insoluble inclusion bodies when overexpressed for protein purification, here (data not shown) and in previous studies (12, 27). Therefore, the solubility of HrpL and HrpL ΔR4.2 was maintained via copurification in complex with an E. coli RNAP with a His tag at the β subunit (28).…”
Section: Resultssupporting
confidence: 87%
“…Forty-four percent of the set of genes predicted in our work probably differ because the profiles used differ in the set of hrp boxes and the alignment of the training set. As in previous work (16,17,26,37,40), our profiles are conserved in the Ϫ35 region of the promoter sequences; however, they differ in the spacer region length and the Ϫ10 region (GGAAC-19-20-ACNNA). These differences are enough to identify different promoter sequences on the same genome or produce different scores.…”
Section: Discussionsupporting
confidence: 82%
“…phaseolicola 1448A (16,17) and hrp boxes characterized in E. amylovora (31). The recent work of Yang et al (40) identified 73 genes preceded by putative hrp boxes in Dickeya dadantii using HMM profiles based on a training set of 69 hrp boxes from E. amylovora, D. dadantii, Pectobacterium atrosepticum, and P. syringae. Only one orthologous gene was common to our findings.…”
Section: Discussionmentioning
confidence: 99%
“…This package aims to identify a specific secretion signal in the N-terminal region of bacterial proteins. An alternative approach to identification of type III effectors, taking into account genomic context, would be to identify the distinctive HrpL alternative sigma factor binding site often found upstream of type III effector genes (Yang et al, 2010; Baltrus et al, 2011; McNally et al, 2011). In general, expression in parasitic life stages is a useful criterion for identifying candidate effector genes, and so tools for the prediction or identification of promotor binding sites are an area we hope to incorporate into our Galaxy setup.…”
Section: Resultsmentioning
confidence: 99%